الوعی المعلوماتی لأعضاء هیئة التدریس بکلیة الآداب الزاویة جامعة الزاویة: دراسة للواقع مع التخطیط للمستقبل - د. عبد العزیز عبد الحمید عامر (المجلة الدولية لعلوم المكتبات والمعلومات)
Information literacy is considered an indicator as it showed technology advances and communication revolution; especially the internet which makes information available for everybody everywhere in the globe. Information literacy has become a strength factor for those who has the technology skills specially in the academic sector. The current research study examines the information literacy of the faculty members in the college of arts at University of Zawia. It aims to explain the importance and goals of the information literacy. It also tries to explain the levels of the information literacy based on the various prospectives. This paper aims to see whether the faculty members have the information literacy skills, the ability to search in the information sources, and the ability to develop all of these skills. The current study used a descriptive case study which examined the participants in details and provided a number of findings. These findings showed some problems and obstacles that face the participants in information literacy. This study ended with some recommendations which will help overcome these problems and obstacles and, in return, improve the information literacy of the faculty members and academic sector in general